“It’s all about making choices”: Paradigms of moral practice in a Catholic Primary School - Grabowski, Karol Franciszek-Maria (2022)
The research undertaken for this investigation took place at a time when social media gave greater exposure to morally questionable actions by prominent politicians and celebrities. At the same time, faith schools underwent a major change in their structure as Multi-Academy Trusts were set up across diocesan regions. The social milieu that existed leads to serious concerns about the moral atmosphere that exists in the so-called “meta-verse” and its impact on both the well-being of children and their moral development. This research was an ethnographic study of a single Roman Catholic primary school and explored the perceptions of various actors, consisting of children and adults, and their interactions as a community of faith that strives to negotiate this moral maze in a period of societal and educational upheaval. The study works at an interface between a range of psychological theories, the moral doctrine of the Roman Catholic Church, and the Ecological Theory of Bronfenbrenner which posits the interaction of multiple factors that influence the final outcomes in the moral development of the children concerned. The findings from observations, field notes, and a series of interviews with teachers and pupils at the school are explored through these three lenses. Findings suggest that the school is in a strong position to resist the onslaught of secularisation and academisation. Children are offered a range of experiences which enable moral growth to take place in a supportive environment which interprets the teachings of the Catholic Church in terms of the many ecologies which the children inhabit. Implications suggest an ongoing need for adult formation, both in parishes and in the teaching profession, if a truly Catholic moral environment is to be sustained in homes and schools.